Paciente femenino de 62 años con tromboembolismo pulmonar. - Burgos León, Erik Fabián (2021)
Pulmonary thromboembolism is usually the occlusion of a blood clot that comes from the venous system, therefore it will be linked to deep vein thrombosis (DVT), evaluating that approximately 10% of these will produce a pulmonary thromboembolism (PE). Less frequently the embolized material can be air, bone fat, amniotic fluid, accumulations of bacteria or paracytes. The incidence of all these is low. This occlusion mainly affects the lungs and the heart, in the heart it will continue to pump but due to the obstacle the pressure increases within the pulmonary artery. Pulmonary thromboembolism is a pathology with high morbidity and mortality, this occurs, frequently producing small embolisms that stop null or scarce clinical percussion as well as the difficulties for its diagnosis, especially non-admitted patients. It is a frequent pathology, whose real incidence is difficult to know due to its great clinical variability, and with an initial mortality that can reach up to 11%, most of it occurring in the first hours of the episode. When the patient is not diagnosed, the mortality of the disease due to relapse is higher than if the patient is treated.